THE STUDY OF THE STATE FREIGHT CAR TRUCKS IMPACT ON SIDE WEAR OF WHEEL FLANGES ON THE RESULTS OF MATHEMATICAL MODELING AND EXAMINATION OF CARS OPERATION - Orlova, A. M.; Lisnychii, V. S.; Artamonov, Ye. I. (Science and Transport Progress, 2008)
In the article the results of mathematical simulation of flange wear of freight wagon wheel in dependence on the bogie conditions (wear-resistant wheel profile, difference of bases on both sides, wear of wedge, difference of diameters of wheels) as well as the results of survey of bogies under operation are presented. The obtained correlation relationships of parameters allowed to estimate the efficiency of measures on reducing the side wear of wheel flanges.